Indicators of sustainability in vocational education and training institutions - Hatos, Hajnalka; Szombathelyi, Márta Konczos (International Journal of Innovative Research and Scientific Studies, 2025)
The paper presents the indicators of sustainability in vocational education and training institutions (VET), which define the tasks of the institutions according to the VET 4.0 strategy and the European Union's objectives. The purpose of this paper is to present and analyze the role of VET in raising awareness of changing economic and social practices and habits that damage the environment in order to ensure the living conditions of present and future generations. The research was conducted among the institutions of a vocational training center, using management interviews, data collection, and document analysis as research methods for examining easily traceable indicators of education in terms of human, social, natural, and economic resources. The main findings show that vocational education and training institutions also play a key role in sustainability. In addition to their educational tasks, another important task is to increase their efficiency and effectiveness in the area of sustainability. The conclusion of the work is that these schools can achieve sustainable development through preventive actions. As a practical implication, the VET needs to be aware of their energy consumption, their choice of means of transport, and the avoidance and prevention of pollution. They have to implement sustainable operations and education for sustainability both inside and outside of school.